Impulse Buying Pada Produk Sociolla: Dianalisis Melalui Promosi Dan Atmosfer Toko - Sopi Fadilah; Rahyuniati Setiawan; Wufron Wufron (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research seeks to analyze how promotional activities and store ambiance influence impulse purchases of Sociolla products. The methodology employed is quantitative, utilizing both descriptive and verificative aspects. Data was gathered by distributing surveys to customers of Sociolla, involving a total of 100 participants. The analysis of the data was conducted using the SmartPLS version 4 software. The findings indicated that both promotion and store ambiance positively and significantly impact impulse purchases of Sociolla products. According to the coefficient of determination analysis, the R-square value recorded was 0. 385, implying that promotion and store ambiance account for 38. 5% of the variance in impulse buying, while the remaining portion is due to factors not included in this research. Results from the bootstrapping test revealed that the promotional variable significantly and positively affects impulse buying, with a T-statistics value of 6. 309 and a P-value of 0. 000. Likewise, the store ambiance variable also showed a significant and positive influence on impulse purchases, yielding a T-statistics value of 2. 345 and a P-value of 0. 019. The promotional variable emerged as the most influential factor affecting consumers' impulse buying behavior toward Sociolla products. In summary, the research concludes that improved promotional strategies and store ambiance lead to an increased likelihood of consumers making impulse purchases of Sociolla products.